2012
DOI: 10.1016/j.aller.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of allergic rhinitis in children: Results of the PETRA study

Abstract: Paediatric patients treated by specialists for allergic rhinitis have moderate or severe disease. Symptomatic treatment was extensively prescribed but often did not achieve good disease control. Many specialists preferred a wait-and-see approach before prescribing immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
2
8
0
2
Order By: Relevance
“…Thus, in Italy 24 patients (23.08 %) of 104 examined children with allergic rhinitis had a mild persistent course; this fact is consistent with our data [15]. In Spain, the moderate course of allergic rhinitis had 63% of the examined children, which is 12% less than our data, but the hypersensitivity to domestic dust mites was registered with a higher frequency and was equal to 61.9 % [16]. Silvia de Magalhaes Simoes and co-authors showed that 143 (36 %) children of 397 children with bronchial asthma had intermittent course; 160 (40 %) -mild persistent course; 51 (12.8 %) -persistent moderate course and 43 (10.8%) -persistent severe course of the disease [17].…”
Section: Resultssupporting
confidence: 91%
“…Thus, in Italy 24 patients (23.08 %) of 104 examined children with allergic rhinitis had a mild persistent course; this fact is consistent with our data [15]. In Spain, the moderate course of allergic rhinitis had 63% of the examined children, which is 12% less than our data, but the hypersensitivity to domestic dust mites was registered with a higher frequency and was equal to 61.9 % [16]. Silvia de Magalhaes Simoes and co-authors showed that 143 (36 %) children of 397 children with bronchial asthma had intermittent course; 160 (40 %) -mild persistent course; 51 (12.8 %) -persistent moderate course and 43 (10.8%) -persistent severe course of the disease [17].…”
Section: Resultssupporting
confidence: 91%
“…These figures are in agreement with previous reports of type of immunotherapy used for AR in Spain but do not fit with recent recommendations and also contrasts with higher use of sublingual immunotherapy in other countries such as France or Italy. The low number of patients treated with specific immunotherapy may be explained by the fact that many specialists prefer to wait and see the evolution of the disease before initiating immunotherapy treatment or because ENT specialists do not tend to prescribe immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, 57% of the patients can experience side effects of these drugs and sufficient symptom control may not be ensured. 11,12 Furthermore, pharmacotherapy may not have an effect on the course of the disease and it is required to have the drugs as long as the patients have the symptoms throughout their life.…”
Section: Discussionmentioning
confidence: 99%